The elements of boat strength : for builders, designers, and owners - Gerr, Dave (International Marine/McGraw-Hill, 2000)
"Author and naval architect Dave Gerr created this unique system of easy-to-use scantling rules and rules-of-thumb for calculating the necessary dimensions, or scantlings, of hulls, decks, and other boat parts, whether built of fiberglass, wood, wood-epoxy composite, steel, or aluminum. In addition to the rules themselves, The Elements of Boat Strength offers their context: an in-depth, plain-English discussion of boatbuilding materials, methods, and practices that will guide you through all aspects of boat construction."--BOOK JACKET.